Cost-Effectiveness of Reinforced Recycled Aggregate Concrete Structures with Fly Ash and Basalt Fibres Under Corrosion: A Life Cycle Cost Analysis - Abdelrahman Abushanab; Vanissorn Vimonsatit (Buildings)
Recent investigations have shown that the mechanical and durability properties of recycled aggregate concrete can be enhanced using fly ash (FA) and structural fibres. However, the financial viability of combining these products in concrete has not yet been evaluated. Therefore, this study assessed the long-term cost-effectiveness of using recycled concrete aggregates (RCA), FA, and basalt fibres (BF) simultaneously in high-rise reinforced concrete buildings exposed to corrosive environments. A life cycle cost analysis was conducted using five variables, two design alternatives, and twelve design scenarios. The analysis followed ISO 15686–5:2017 using a discount rate of 0.5% and a construction-to-material cost ratio of 150%. The components considered in the life cycle cost model included materials, construction, maintenance, and disposal. The results demonstrated that employing RCA, FA, and BF in combination in concrete buildings located near the ocean achieved approximately 21% cost savings compared to buildings made with conventional materials over a lifespan of 50 years. The maintenance component exhibited the most significant cost savings, with an average reduction of about 76% in the maintenance costs for all buildings utilising RCA, FA, and BF. The sensitivity analysis revealed that the proposed building with RCA, FA, and BF remained more cost-effective than the conventional concrete building, even with an increasing RCA-to-natural-aggregate price ratio, construction-to-material cost ratio, and increasing the discount rate to 200%, 250%, and 10%, respectively.